PERSPEKTIF HUKUM EKONOMI SYARIAH TENTANG WAKAF UANG DI ERA REVOLUSI INDUSTRI 4.0 - hisam ahyani (J-EBI (Jurnal Ekonomi Bisnis Islam), 2022)
Introduction/Main Objectives: This study aims to determine cash waqf in the view of sharia economic law in the era of the industrial revolution 4.0. Background Problems: The understanding of the Indonesian people regarding cash waqf is still minimal. Even though this waqf has great potential for the welfare of the Indonesian people. Novelty: Regarding research from the perspective of Islamic economic law on cash waqf in the era of the industrial revolution 4.0, no one has researched it. Research Methods: The method used is literature research, qualitative, with statutory, historical, comparative and conceptual approaches and this research is normative. Finding/Results: The view of Shariāh Economics in Indonesia regarding cash waqf is carried out in accordance with Law No.41 / 2004 concerning waqf in which moving objects are in the form of